Practice of Early Initiation of Breastfeeding in Sukoharjo Based on the Theory of Planned Behavior and Social Cognitive Theory (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Early initiation of breastfeeding (IMD) can reduce child mortality. The Sukoharjo district government trained birth attendants to practice of IMD. This qualitative study analyzed the practice of IMD in Sukoharjo. The theme of the results was: the practice of IMD in Sukoharjo seen from the Theory of Planned Behavior and Social Cognitive Theory. The categories found were: 1) There were several obstacles and support, 2) not all mothers had the intention to practice early initiation of breastfeeding (IMD), 3) in general, hospitals had not properly practiced IMD, 4) families did not obstruct IMD, 5) not all community health center implemented IMD according to standards, 6) not all birth attendants understood IMD correctly, 7) neighbors did not understand the importance of IMD, 8) not all mothers understood or asked for IMD before delivery, 9) birth attendants perceived that IMD was not burdensome, 10) health workers supported IMD, 11) there was government support, 12) mothers and birth attendants had good health expectations related to IMD, 13) the standard of IMD in Sukoharjo has been partially met. The conclusion is that the IMD in Sukoharjo was already underway but still needed a lot of improvement. When viewed from the TPB and SCT theory, some of the constructs were strong, but many of them were weak. Both of these theories can be used as a basis for interventions to improve the IMD.